2022
DOI: 10.3390/w14162584
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Total Nitrogen and Phosphorus Variation, Speciation, and Composition in the Maowei Sea Affected by Riverine Flux Input, South China Sea

Abstract: Human activities have altered global nutrient cycling and have significantly changed marine systems. This is evidenced by the significant changes in nitrogen and phosphorus availability. The Maowei Sea (MWS) is the largest oyster culture bay in southwest China. From August 2018 to May 2019, the spatial and temporal nutrient concentrations and fluxes in MWS using system-wide scale seasonal data were assessed from river estuaries and adjacent coastal waters. The annual average concentrations of total nitrogen (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 76 publications
1
1
0
Order By: Relevance
“…Our results showed that the DIN content in the Qiongzhou Strait is higher in spring, which is similar to the research conclusions of Wei and others, where the DIN content in spring was higher than that in autumn [24]. A few studies discovered this time distribution rule for DIN in the surrounding sea area of Hainan Island [23,25,26]. In this study, the main component of DIN was NH 4 -N, which may come from the large amount of aquaculture activities along the north coast of the strait [27].…”
Section: Hydrodynamic Factors and Artificial Activities Impacting Wat...supporting
confidence: 91%
“…Our results showed that the DIN content in the Qiongzhou Strait is higher in spring, which is similar to the research conclusions of Wei and others, where the DIN content in spring was higher than that in autumn [24]. A few studies discovered this time distribution rule for DIN in the surrounding sea area of Hainan Island [23,25,26]. In this study, the main component of DIN was NH 4 -N, which may come from the large amount of aquaculture activities along the north coast of the strait [27].…”
Section: Hydrodynamic Factors and Artificial Activities Impacting Wat...supporting
confidence: 91%
“…There is a significant negative linear relationship between DIN, DIP, and COD and salinity in Tieshan Bay coastal water in each season (p < 0.05) (Figure 9), proving that the main controlling factor of DIN, DIP, and COD spatial changes may be the input of fresh water in rivers [12,28,72]. However, the decreasing trend of different environmental factors with salinity may be related to the degree of freshwater input and land-based pollutant input [68,73].…”
Section: Effects Of the Riverine Freshwater Input On Din Dip And Cod ...mentioning
confidence: 94%
“…In the laboratory, multiple standard solutions of different concentrations are measured to establish the relationship between absorbance and concentration. Each measurement project utilizes its own specific standard curve [6] .…”
Section: Measurement Principlementioning
confidence: 99%